2021
DOI: 10.3126/ijosh.v11i2.37253
|View full text |Cite
|
Sign up to set email alerts
|

Challenges of limited reuse and extended use of N95 filtering facepiece respirators: Lesson learnt from COVID-19 pandemic in Mumbai, India

Abstract: Introduction: Usage of personal protective equipment, which includes N95 filtering face piece respirators (FFRs), was the major preventive measure for healthcare workers to control COVID-19 transmission. However, a global shortage of N95 FFRs was observed worldwide during initial phase of pandemic. Reusing mask was the only strategy and various decontamination methods were suggested. The main objective of the study was to evaluate the compliance rate of limited reuse and extended use policy implemented in hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
1
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 4 publications
3
1
0
6
Order By: Relevance
“…When evaluating the integrity of the N95/PFF2 masks reused for seven and fifteen days, several signs of wear on the straps and degradation on the nose clips were identified through visual inspection. These damages corroborate the findings of studies carried out in both clinical and laboratory environments, highlighting the fragility of this equipment under reuse conditions ( 9 , 25 ) . A clinical study, carried out in a tertiary hospital in India during the COVID-19 pandemic, indicated that 9% of health professionals reported the loosening of straps, generally after five reuses in eight-hour shifts, as one of the main reasons for early disposal of N95/PFF2 masks ( 25 ) .…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…When evaluating the integrity of the N95/PFF2 masks reused for seven and fifteen days, several signs of wear on the straps and degradation on the nose clips were identified through visual inspection. These damages corroborate the findings of studies carried out in both clinical and laboratory environments, highlighting the fragility of this equipment under reuse conditions ( 9 , 25 ) . A clinical study, carried out in a tertiary hospital in India during the COVID-19 pandemic, indicated that 9% of health professionals reported the loosening of straps, generally after five reuses in eight-hour shifts, as one of the main reasons for early disposal of N95/PFF2 masks ( 25 ) .…”
Section: Discussionsupporting
confidence: 88%
“…These damages corroborate the findings of studies carried out in both clinical and laboratory environments, highlighting the fragility of this equipment under reuse conditions ( 9 , 25 ) . A clinical study, carried out in a tertiary hospital in India during the COVID-19 pandemic, indicated that 9% of health professionals reported the loosening of straps, generally after five reuses in eight-hour shifts, as one of the main reasons for early disposal of N95/PFF2 masks ( 25 ) . In a laboratory context, simulating a ten-hour shift, it was found that the rupture of five nose clips and eight fixation items, which occurred over 20 episodes of donning and doffing, resulted in the failure of sealing tests for all participants who used such devices ( 9 ) .…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Self-quarantine for several weeks, confusion about the symptoms of the disease will last even after getting cured. 17,18 In such cases, the organization should come forward to address the problems of such people rather than just ignoring them. Strategies that are devised to isolate people from getting the infection, may sometimes affect their mental health leading to stress.…”
Section: Post-covid Behavioural Changesmentioning
confidence: 99%